1991
DOI: 10.1104/pp.95.1.184
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to Thylakoid Composition during Development of Maize Leaves at Low Growth Temperatures

Abstract: The effects of reductions in growth temperature on the development of thylakoids of maize (Zea mays var LG11) leaves are examined. Thylakoids isolated from mesophyll cells of leaves grown at 170 and 140C, compared with 250C, exhibited a decreased accumulation of many polypeptides, which was accompanied by a loss of activity of photosystems (PS) I and I. Probing the polypeptide profiles with a range of antibodies specific for thylakoid proteins demonstrated that a number of polypeptides encoded by the chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
64
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 26 publications
11
64
0
Order By: Relevance
“…This agrees with the results of other experiments made on cold-stressed plants, where the increased efficiency of electron transport around PS1 complex was observed (Sonoike 1998, Pessarakli 1999. PS1 is probably less susceptible to low temperature-induced damage compared to PS2, particularly under low-light conditions when no photodamage to this complex should occur (Nie and Baker 1991, Körnerová and Holá 1999, Sonoike 1998, Pessarakli 1999. All three biotypes examined responded to the cultivation at 10°C by an increase of the PS1 activity; this increase was slightly higher in the atrazine-sensitive biotypes Jihlava and Karlín than in the resistant biotype Bubny (Figure 4).…”
Section: Resultssupporting
confidence: 92%
“…This agrees with the results of other experiments made on cold-stressed plants, where the increased efficiency of electron transport around PS1 complex was observed (Sonoike 1998, Pessarakli 1999. PS1 is probably less susceptible to low temperature-induced damage compared to PS2, particularly under low-light conditions when no photodamage to this complex should occur (Nie and Baker 1991, Körnerová and Holá 1999, Sonoike 1998, Pessarakli 1999. All three biotypes examined responded to the cultivation at 10°C by an increase of the PS1 activity; this increase was slightly higher in the atrazine-sensitive biotypes Jihlava and Karlín than in the resistant biotype Bubny (Figure 4).…”
Section: Resultssupporting
confidence: 92%
“…After three weeks of chilling treatment chilled plants had fewer leaves and internodes in comparison with non-chilled ones (Table 1, Figure 1A, B). Decrease in growth rate, but no effects on plant ontogeny, were observed by Nie and Baker (1991), Nie et al (1992), Sowinski et al (2003). Sowinski et al (2003) also found thicker leaf blades in chilled maize plants.…”
Section: Growth Characteristicsmentioning
confidence: 80%
“…Low spring temperatures can seriously damage growth and ontogeny of young maize plants due to the inhibition of their photosynthesis (Nie and Baker 1991, Nie et al 1992, Dolstra et al 1994, Massacci et al 1995. Maize as a biological species includes a large number of genotypes which differ in their tolerance to low temperatures (chilling or cold) (Dolstra et al 1994, Massacci et al 1995.…”
mentioning
confidence: 99%
“…Nie and Baker (1991) reported that although re-exposure to the optimal temperatures caused a rapid synthesis and accumulation of pigments and many proteins to levels close to those found in the leaves grown at 25°C, the leaves do not attain similar levels of photosynthetic competence. It is possible that the exposure to low temperature during early stages of leaf development restricts the synthesis of components essential for the thylakoid development, which cannot be made at later stages of leaf development when the temperature increases.…”
Section: Resultsmentioning
confidence: 96%
“…It is known that chilling in the light sensitize photosynthesis to photoinhibition (Xu et al 1999), which results in bleaching of photosynthetic pigments (Nie and Baker 1991). A decrease in the chlorophyll content was suggested to reduce the absorption of potentially damaging light and therefore the risk of singlet oxygen formation is relatively lower (Leipner et al 2000).…”
Section: Resultsmentioning
confidence: 99%